1993
DOI: 10.1055/s-2007-994657
|View full text |Cite
|
Sign up to set email alerts
|

General Anesthesia for Surgical Repair of Intracranial Aneurysm in Pregnancy: Effects on Fetal Heart Rate

Abstract: A 30-year-old nulliparous woman underwent surgery for a ruptured aneurysm of the left vertebral artery in gestational week 27. The fetal heart rate (FHR) was monitored continuously with an abdominal Doppler transducer. Anesthesia was induced with midazolam, fentanyl, and thiopental and maintained with fentanyl, isoflurane, and nitrous oxide 67% in oxygen. Surgery was performed under moderate hypotension (mean arterial pressure +/- 70 mmHg) and moderate hyperventilation (arterial carbon dioxide pressure +/- 33 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 8 publications
(16 reference statements)
1
11
0
1
Order By: Relevance
“…Cerebral aneurysmal complications occur exceptionally during pregnancy and have generally been reported in the literature in the form of a case report (1–11). Their low frequency may be explained by the mean age of aneurysmal rupture in women, which is approximately the age of 50 (12,17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cerebral aneurysmal complications occur exceptionally during pregnancy and have generally been reported in the literature in the form of a case report (1–11). Their low frequency may be explained by the mean age of aneurysmal rupture in women, which is approximately the age of 50 (12,17).…”
Section: Discussionmentioning
confidence: 99%
“…It would be impossible to decide on a dominant carotid topography in pregnancy based on only eight cases and this remains to be confirmed by a large retrospective study. However, we reviewed other pregnant cases presented in the past 17 years' literature and we found that seven cases out of 14 described an ICA aneurysm (2–10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…49) However, cesarean delivery has several limitations in the angiographic suite with limited equipment. A hybrid operating room equipped with a full-spec digital subtraction angiography machine is considered to be useful.…”
Section: Subarachnoid Hemorrhage (Sah)mentioning
confidence: 99%